Stapled peptides: Magic bullets in nature's arsenal. - Kritzer, Joshua A. (Tufts University. Tisch Library., 2017)
Selectivity is a key obstacle in drug development. A new study describes how "peptide stapling," a technique for making peptide α-helices more potent and cell permeable, allows the design of MCL-1 inhibitors with extraordinary selectivity.